A cross-linked polyethylene insulated low-smoke halogen-free power composite cable and a preparation method thereof
Patent Information
- Application Number
- CN202611490657.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-23
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]现有技术主要通过结构隔离、支承和屏蔽保持网络传输性能,或通过增加无机阻燃剂、相容剂及成炭组分提高护套料的阻燃性能,高填充低烟无卤材料通常采用各组分共同混炼的方式,以促进填料分散和界面结合,然而,填料与树脂之间结合过强时,内护套在电力线芯反复升温和冷却过程中产生的压缩应力不易释放,容易对相邻网络单元形成持续变化的压紧作用,影响其特性阻抗、回波损耗及串音性能,若通过增加弹性体、减少阻燃填料或降低内护套硬度减小约束等方式,又会削弱内护套的阻燃和结构支承性能
[0017]本发明中,通过改变低烟无卤内护套料中各无机组分的混炼顺序,本发明先使氢氧化铝和氢氧化镁在树脂熔体中完成主体润湿,再加入水滑石对剩余酸性活性基团进行有限终止处理,随后加入硼酸锌及其余助剂,并以水滑石处理前后可提取聚合物相酸值的比值控制有限终止程度,区别于现有技术将树脂、相容剂和无机组分共同混炼的制备方式,由此避免填料与树脂之间的界面结合过强或受限过度,使内护套在保持阻燃、抑烟、力学性能和结构支承能力的同时,具备较好的高温压缩应力松弛及形变恢复性能,减小电力线芯反复升温和冷却时内护套对CAT6 SFTP网络单元产生的压紧作用,从而提高复合缆特性阻抗、回波损耗及串音性能的稳定性。
Smart Images

Figure CN123017637A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of cable technology, and in particular to a cross-linked polyethylene insulated low-smoke halogen-free power composite cable and its preparation method. Background Technology
[0002] With the development of smart buildings, industrial internet, urban integrated pipe corridors, and security systems, power supply lines and data communication lines need to be laid simultaneously. Integrating power conductors and network transmission units into the same cable can reduce the number of lines and laying space, and lower construction costs. In addition to meeting the requirements of power transmission and network transmission, these composite cables also need to have low smoke and halogen-free properties, flame retardancy, shielding, and mechanical protection. For composite cables using cross-linked polyethylene insulation and Category 6 network units, the power conductors experience temperature changes when carrying current, while the network units are more sensitive to the position of the wire pairs and external forces. Therefore, the sheath material also needs to take into account the stability of network transmission.
[0003] Existing technologies have researched composite structures for electrical and network cables and low-smoke halogen-free cable materials. Patent CN114093555A discloses a composite cable for electrical and network cables, which incorporates differential signal cores, power cores, control cores, and coaxial signal cores within the cable core, and maintains the structural stability of the signal cores through a skeleton, wrapping tape, and shielding layer. Patent CN116102815A discloses an irradiated crosslinked low-smoke halogen-free insulation material, using ethylene-vinyl acetate, elastomers, linear low-density polyethylene, and maleic anhydride-grafted polyethylene as base materials, and incorporating aluminum hydroxide, magnesium hydroxide, and crosslinking aids to improve the insulation material's heat resistance, flame retardancy, and mechanical properties. Patent CN119684704A discloses a B1-grade cable material, employing various polyolefin resins, maleic anhydride graft compatibilizers, aluminum hydroxide, magnesium hydroxide, hydrotalcite, and smoke-suppressing and char-forming components to improve the flame retardant properties of the cable sheathing material.
[0004] Existing technologies mainly maintain network transmission performance through structural isolation, support, and shielding, or improve the flame retardant properties of the sheath material by adding inorganic flame retardants, compatibilizers, and char-forming components. High-filler, low-smoke, halogen-free materials are usually produced by co-mixing the components to promote filler dispersion and interfacial bonding. However, when the bond between the filler and the resin is too strong, the compressive stress generated by the inner sheath during the repeated heating and cooling of the power line core is not easily released, which can easily create a continuously changing compression effect on adjacent network units, affecting their characteristic impedance, return loss, and crosstalk performance. If the flame retardant filler is reduced, or the hardness of the inner sheath is reduced to decrease the constraint, the flame retardant and structural support performance of the inner sheath will be weakened. Summary of the Invention
[0005] The technical problem to be solved by this invention is: how to reduce the impact of current-carrying temperature changes on the transmission stability of network units while maintaining the flame-retardant and support performance of the inner sheath. To this end, we propose a cross-linked polyethylene insulated low-smoke halogen-free power composite cable and its preparation method.
[0006] To achieve the above objectives, this application adopts the following technical solution: a method for preparing a cross-linked polyethylene insulated low-smoke halogen-free power composite cable, comprising the following steps: S1: adding ethylene-vinyl acetate copolymer, linear low-density polyethylene, polyolefin elastomer, metallocene polyethylene, and maleic anhydride-grafted polyolefin into a mixer, and mixing at 110-120℃ until all resins are fully melted to obtain a molten material; S2: adding all aluminum hydroxide and magnesium hydroxide to the molten material, raising the material temperature to 125-135℃, and continuing to mix for 4-8 minutes. S3: The temperature of the main wetting material is reduced to 115-123℃, hydrotalcite is added and mixing is continued. The extractable polymer phase acid value of the main wetting material before the addition of hydrotalcite is recorded as V1, and the extractable polymer phase acid value of the material after mixing with hydrotalcite is recorded as V2. The ratio of V2 to V1 is 0.55-0.75. S4: After mixing, zinc borate is added to the material, and after mixing, the material is discharged. The resulting mixture is then extruded and granulated to obtain a low-smoke halogen-free inner sheath material. S5: The power core with irradiated cross-linked polyethylene insulation layer, CAT6 SFTP network unit and low-smoke halogen-free flame-retardant filler are twisted together to form a composite cable core. The first wrapping layer, the second wrapping layer and the total shielding layer are formed sequentially on the outside of the composite cable core. The low-smoke halogen-free inner sheath material is extruded on the outside of the total shielding layer to form a low-smoke halogen-free inner sheath. Then, the steel tape armor layer and the low-smoke halogen-free outer sheath are formed sequentially to obtain the power composite cable.
[0007] Preferably, in S2, after aluminum hydroxide and magnesium hydroxide are added, the mixing torque first rises to a peak value, and then gradually decreases during the mixing process. When the torque decreases by 12-22% relative to the peak value, and the torque fluctuation within the following 60-90 seconds does not exceed ±3% of the stable torque value, the main body wetting is ended.
[0008] Preferably, in S3, after adding hydrotalcite, the mixing continues for 1.5-3.5 minutes to perform a limited termination treatment on the main wetted material.
[0009] Preferably, after the limited termination treatment, the material temperature is maintained at 112-122℃, zinc borate, silicone masterbatch, lubricant and color masterbatch are added, and the mixture is continued to be mixed for 1.5-3 minutes before being discharged.
[0010] Preferably, the total time from the addition of the hydrotalcite to the discharge of the material in the internal mixer does not exceed 5 minutes.
[0011] Preferably, before preparing the low-smoke halogen-free inner sheath material, aluminum hydroxide, magnesium hydroxide, hydrotalcite and zinc borate are dried at 95-105℃ for 2-4 hours.
[0012] Preferably, the free water content of the aluminum hydroxide and magnesium hydroxide is not higher than 0.2%, and the free water content of the hydrotalcite and zinc borate is not higher than 0.5%.
[0013] A cross-linked polyethylene insulated low-smoke halogen-free power composite cable includes a composite cable core and a first wrapping layer, a second wrapping layer, a total shielding layer, a low-smoke halogen-free inner sheath, a steel tape armor layer, and a low-smoke halogen-free outer sheath sequentially wrapped around the composite cable core. The material of the low-smoke halogen-free inner sheath, based on a total resin matrix of 100 parts, includes 40-48 parts of ethylene-vinyl acetate copolymer, 16-24 parts of linear low-density polyethylene, 18-26 parts of polyolefin elastomer, 5-10 parts of metallocene polyethylene and 8-12 parts of maleic anhydride-grafted polyolefin, 90-105 parts of aluminum hydroxide, 28-40 parts of magnesium hydroxide, 3-5 parts of hydrotalcite and 4-7 parts of zinc borate.
[0014] Preferably, the composite cable core is formed by stranding together a power wire core with an irradiated cross-linked polyethylene insulation layer, a CAT6 SFTP network unit, and a low-smoke halogen-free flame-retardant filler material.
[0015] Preferably, based on 100 parts of resin matrix, the material of the low-smoke halogen-free inner sheath also includes 2-4 parts of silicone masterbatch, 0.8-1.5 parts of composite antioxidant, 1.0-2.0 parts of lubricant and 1.0-2.0 parts of color masterbatch.
[0016] The technical effects and advantages of this invention are as follows:
[0017] In this invention, by changing the mixing order of the inorganic components in the low-smoke halogen-free inner sheath material, aluminum hydroxide and magnesium hydroxide are first used to complete the main wetting in the resin melt. Then, hydrotalcite is added to perform limited termination treatment on the remaining acidic active groups. Subsequently, zinc borate and other additives are added, and the degree of limited termination is controlled by the ratio of the extractable polymer phase acid value before and after hydrotalcite treatment. This method differs from the existing technology that uses resin, compatibilizer and inorganic components to be mixed together. This avoids excessively strong or restricted interfacial bonding between the filler and the resin, so that the inner sheath can maintain flame retardancy, smoke suppression, mechanical properties and structural support capacity, while having better high-temperature compressive stress relaxation and deformation recovery performance. It also reduces the compressive effect of the inner sheath on the CAT6 SFTP network unit when the power conductor core is repeatedly heated and cooled, thereby improving the stability of the composite cable's characteristic impedance, return loss and crosstalk performance. Attached Figure Description
[0018] The disclosure of this invention is illustrated with reference to the accompanying drawings. It should be understood that the drawings are for illustrative purposes only and are not intended to limit the scope of protection of this invention. In the drawings:
[0019] Figure 1 The graph shows the relationship between the mixing time of hydrotalcite and V2 / V1, the compressive stress retention rate, and the thickness recovery rate. Detailed Implementation
[0020] In this embodiment, all raw materials used are commercially available industrial-grade products. The amount of each component is calculated by mass parts. The insulation material, inner sheath material and outer sheath material are all measured based on a total resin matrix of 100 parts.
[0021] All embodiments and comparative examples use the same batch of raw materials. Except for the formula or process variables explicitly described in each example, the power conductor insulation material, CAT6 SFTP network unit and outer sheath material used are the same, and the cable structure, specifications and manufacturing conditions are consistent.
[0022] The power composite cable prepared in this embodiment includes a composite cable core and a first wrapping layer, a second wrapping layer, a total shielding layer, a low-smoke halogen-free inner sheath, a steel tape armor layer, and a low-smoke halogen-free outer sheath sequentially wrapped around the composite cable core.
[0023] The composite cable core consists of three conductors with a nominal cross-sectional area of 2.5 mm². 2 It is formed by twisting together a power conductor core, a CAT6 SFTP network unit, and low-smoke halogen-free flame-retardant filler material.
[0024] Each power conductor core includes a stranded copper conductor and an irradiated cross-linked polyethylene insulation layer extruded over the stranded copper conductor. The stranded copper conductor is formed by stranding annealed soft copper wires, and the rated voltage of the power conductor core is 300V.
[0025] The communication insulation layer of the CAT6 SFTP network unit is made of high-density polyethylene material. The shielding structure includes an aluminum foil shielding layer and a tinned copper wire braided shielding layer outside the aluminum foil shielding layer. The braiding coverage of the tinned copper wire braided shielding layer is 80%. A low-smoke halogen-free flame-retardant polyolefin sheath is extruded outside the tinned copper wire braided shielding layer. The characteristic impedance of the CAT6 SFTP network unit is 100±10Ω.
[0026] Low-smoke halogen-free flame-retardant filler material is placed in the gap between the three power line cores and the CAT6 SFTP network unit. The first wrapping layer is formed by wrapping with polyester film tape, the second wrapping layer is formed by wrapping with low-smoke halogen-free glass fiber reinforced flame-retardant tape, the total shielding layer is formed by braiding with tin-plated soft copper wire, and the steel tape armor layer is formed by wrapping with galvanized steel tape.
[0027] The ethylene-vinyl acetate copolymer used to prepare the low-smoke halogen-free inner sheath material has a vinyl acetate content of 26% by mass and a melt flow rate of 4.0 g / 10 min; the linear low-density polyethylene has a density of 0.920 g / cm³. 3 The melt flow rate is 2.0 g / 10 min; the polyolefin elastomer is an ethylene-octene copolymer with a density of 0.870 g / cm³. 3 The melt flow rate is 1.0 g / 10 min, the Shore A hardness is 85, and the density of metallocene polyethylene is 0.918 g / cm³. 3 The melt mass flow rate was 1.0 g / 10 min, and all of the above melt mass flow rates were measured at 190 °C and 2.16 kg.
[0028] The maleic anhydride-grafted polyolefin used in this embodiment is maleic anhydride-grafted polyethylene with a maleic anhydride grafting rate of 0.9% and a melt mass flow rate of 1.5 g / 10 min measured at 190°C and 2.16 kg. Aluminum hydroxide and magnesium hydroxide are both silane-surface-treated powders with median particle sizes D50 of 1.8 μm and 2.5 μm, respectively. Hydrotalcite is magnesium aluminum hydrotalcite with hydrogenated fatty acid surface treatment, with a median particle size D50 of 1.2 μm and a surface treatment agent mass content of 1.0%. Zinc borate is hydrated zinc borate with the composition 2ZnO·3B2O3·3.5H2O and a median particle size D50 of 3.1 μm.
[0029] The silicone masterbatch uses polyethylene as a carrier, in which the mass content of polydimethylsiloxane is 50%; the composite antioxidant is composed of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1; the lubricant is polyethylene wax with a dropping point of 105℃; the color masterbatch uses polyethylene as a carrier, in which the mass content of pigment is 40%.
[0030] In this embodiment, the low-smoke halogen-free inner sheath material, based on a total of 100 parts of resin matrix, includes 40-48 parts of ethylene-vinyl acetate copolymer, 16-24 parts of linear low-density polyethylene, 18-26 parts of polyolefin elastomer, 5-10 parts of metallocene polyethylene, and 8-12 parts of maleic anhydride-grafted polyolefin. The resin components are adjusted within the above range and totaled to 100 parts.
[0031] The low-smoke halogen-free inner sheath material also includes 90-105 parts aluminum hydroxide, 28-40 parts magnesium hydroxide, 3-5 parts hydrotalcite, 4-7 parts zinc borate, 2-4 parts silicone masterbatch, 0.8-1.5 parts composite antioxidant, 1.0-2.0 parts lubricant, and 1.0-2.0 parts color masterbatch.
[0032] Before preparing the low-smoke halogen-free inner sheath material, aluminum hydroxide, magnesium hydroxide, hydrotalcite and zinc borate are dried at 95-105℃ for 2-4 hours, so that the free moisture content of aluminum hydroxide and magnesium hydroxide is ≤0.2%, and the free moisture content of hydrotalcite and zinc borate is ≤0.5%.
[0033] Preheat the ethylene-vinyl acetate copolymer, linear low-density polyethylene, polyolefin elastomer, metallocene polyethylene, and maleic anhydride-grafted polyolefin at 50-70℃ for 30-60 minutes.
[0034] Each pretreated raw material was measured separately, with aluminum hydroxide and magnesium hydroxide prepared together, and hydrotalcite and zinc borate measured separately and prepared separately.
[0035] The preparation method of the low-smoke halogen-free inner sheath material includes the following steps.
[0036] S1: Add ethylene-vinyl acetate copolymer, linear low-density polyethylene, polyolefin elastomer, metallocene polyethylene, maleic anhydride-grafted polyolefin and composite antioxidant to a mixer and mix at 110-120°C until all resins are fully melted and form a continuous molten material.
[0037] S2: Add all aluminum hydroxide and magnesium hydroxide to the resulting molten material, raise the material temperature to 125-135℃, and continue to knead for 4-8 minutes.
[0038] After aluminum hydroxide and magnesium hydroxide are added, the mixing torque first rises to the peak value, and then gradually decreases during the mixing process. When the torque decreases by 12%-22% relative to the peak value, and the torque fluctuation within the following 60-90 seconds does not exceed ±3% of the stable torque value, the main wetting is ended, and the main wetted material is obtained.
[0039] S3: After the main body is wetted, keep the internal mixer rotor speed at 50 r / min and cool the material temperature to 115-123℃ through jacket cooling. Then add hydrotalcite and continue mixing for 1.5-3.5 min to perform limited termination treatment on the material after the main body is wetted.
[0040] Before adding hydrotalcite, the main wetted material is sampled and its extractable polymer phase acid value is measured and recorded as V1; after the hydrotalcite is mixed, the sample is taken again and the extractable polymer phase acid value of the resulting material is measured and recorded as V2. V2 / V1 is controlled between 0.55 and 0.75.
[0041] S4: After the limited termination process is completed, keep the material temperature at 112-122℃, add zinc borate, silicone masterbatch, lubricant and color masterbatch, continue mixing for 1.5-3 minutes and then discharge the material. The total time from the addition of hydrotalcite to the internal mixer to the discharge of the material should not exceed 5 minutes.
[0042] S5: The discharged mixture is fed into a two-stage extrusion granulation equipment. The first stage uses a twin-screw extruder, and the second stage uses a single-screw extruder. The material temperature during the extrusion process is controlled at 115-130℃, and the maximum material temperature does not exceed 140℃. After pelleting, cooling and drying, the extrudate is sealed and packaged to obtain low-smoke halogen-free inner sheath material.
[0043] The following examples and comparative examples are based on a total resin matrix of 100 parts for the inner sheath material. The only changes in each group are the composition of the inner sheath material, the order of addition of inorganic components, or the degree of limited termination of hydrotalcite.
[0044] Example 1
[0045] The low-smoke halogen-free inner sheath material of this embodiment includes 45 parts ethylene-vinyl acetate copolymer, 20 parts linear low-density polyethylene, 20 parts polyolefin elastomer, 7 parts metallocene polyethylene, 8 parts maleic anhydride grafted polyolefin, 95 parts aluminum hydroxide, 35 parts magnesium hydroxide, 4 parts hydrotalcite, 6 parts zinc borate, 3 parts silicone masterbatch, 1.2 parts composite antioxidant, 1.5 parts lubricant, and 1.5 parts color masterbatch.
[0046] Aluminum hydroxide, magnesium hydroxide, hydrotalcite and zinc borate were dried at 100℃ for 3 hours, and each resin raw material was preheated at 60℃ for 45 minutes.
[0047] Ethylene-vinyl acetate copolymer, linear low-density polyethylene, polyolefin elastomer, metallocene polyethylene, maleic anhydride-grafted polyolefin, and composite antioxidant are added to an internal mixer and mixed at 115°C until all resins are fully melted. Then aluminum hydroxide and magnesium hydroxide are added, and the material temperature is raised to 130°C and the mixing continues. When the mixing torque reaches its peak and then decreases by 17%, and remains stable for the next 75 seconds with torque fluctuations not exceeding ±3% of the stable torque value, the main body wetting is stopped.
[0048] The material temperature was lowered to 119℃, and hydrotalcite was added and mixed for another 2.5 minutes. The ratio of the extractable polymer acid value V2 / V1 before and after the addition of hydrotalcite was controlled to be 0.65. Then zinc borate, silicone masterbatch, lubricant and color masterbatch were added, and the mixture was mixed at 118℃ for another 2 minutes before being discharged. The total time from the addition of hydrotalcite to discharge was 4.5 minutes.
[0049] The discharged mixture is fed into a two-stage extrusion granulation equipment. The material temperature of the first-stage twin-screw extruder is controlled at 120-130℃, and the die head temperature of the second-stage single-screw extruder is 128℃. The highest material temperature during the granulation process does not exceed 140℃. After cooling and drying, the resulting granules are used to obtain low-smoke halogen-free inner sheath material.
[0050] Example 2
[0051] The composition of the inner sheath material in this embodiment is the same as that in Example 1. The difference is that after the main body is wetted and the material temperature is reduced to 119°C, hydrotalcite is added and mixed for 1.8 minutes to control V2 / V1 to 0.727. Then, zinc borate, silicone masterbatch, lubricant and color masterbatch are added according to the method of Example 1. The total time from adding hydrotalcite to discharging is 3.8 minutes. The remaining steps are the same as in Example 1.
[0052] Example 3
[0053] The composition of the inner sheath material in this embodiment is the same as that in Example 1. The difference is that after the main body is wetted and the material temperature is reduced to 119°C, hydrotalcite is added and mixed for 3.2 minutes to control V2 / V1 to 0.570. Then zinc borate, silicone masterbatch, lubricant and color masterbatch are added and mixed at 118°C for 1.5 minutes before being discharged. The total time from adding hydrotalcite to discharge is 4.7 minutes. The remaining steps are the same as in Example 1.
[0054] Example 4
[0055] The low-smoke halogen-free inner sheath material of this embodiment includes 45 parts ethylene-vinyl acetate copolymer, 20 parts linear low-density polyethylene, 20 parts polyolefin elastomer, 7 parts metallocene polyethylene, 8 parts maleic anhydride grafted polyolefin, 95 parts aluminum hydroxide, 35 parts magnesium hydroxide, 3 parts hydrotalcite, 6 parts zinc borate, 3 parts silicone masterbatch, 1.2 parts composite antioxidant, 1.5 parts lubricant, and 1.5 parts color masterbatch.
[0056] The preparation method in this embodiment is the same as in Example 1. The mixing time after adding hydrotalcite is 2.5 min, and the V2 / V1 ratio is controlled at 0.686. Except for the amount of hydrotalcite being adjusted to 3 parts, the amount of other raw materials and operating conditions are the same as in Example 1.
[0057] Example 5
[0058] The low-smoke halogen-free inner sheath material of this embodiment includes 45 parts ethylene-vinyl acetate copolymer, 20 parts linear low-density polyethylene, 20 parts polyolefin elastomer, 7 parts metallocene polyethylene, 8 parts maleic anhydride grafted polyolefin, 95 parts aluminum hydroxide, 35 parts magnesium hydroxide, 5 parts hydrotalcite, 6 parts zinc borate, 3 parts silicone masterbatch, 1.2 parts composite antioxidant, 1.5 parts lubricant, and 1.5 parts color masterbatch.
[0059] The preparation method in this embodiment is the same as in Example 1. The mixing time after adding hydrotalcite is 2.5 min, and the V2 / V1 ratio is controlled at 0.594. Except for the amount of hydrotalcite being adjusted to 5 parts, the amount of other raw materials and operating conditions are the same as in Example 1.
[0060] Comparative Example 1
[0061] The composition of the inner sheath material in this comparative example is the same as that in Example 1, except that the inner sheath material is prepared by co-mixing.
[0062] The resins and composite antioxidants were mixed at 115°C until fully melted. At the same time, aluminum hydroxide, magnesium hydroxide, hydrotalcite, zinc borate, silicone masterbatch, lubricant and color masterbatch were added. The material temperature was raised to 130°C and continued to be mixed for 8 minutes. After the material was evenly mixed and the torque tended to be stable, the material was discharged and then two-stage extrusion granulation was carried out according to the conditions of Example 1.
[0063] Comparative Example 2
[0064] The composition of the inner sheath material in this comparative example is the same as that in Example 1, except that hydrotalcite, aluminum hydroxide, and magnesium hydroxide are added simultaneously.
[0065] The resins and composite antioxidants were mixed at 115°C until fully melted. Aluminum hydroxide, magnesium hydroxide and hydrotalcite were added at the same time. The material temperature was raised to 130°C and the mixing was continued. After the torque reached its peak, it decreased by 17% and remained stable for the next 75 seconds. The material temperature was then lowered to 119°C. Zinc borate, silicone masterbatch, lubricant and color masterbatch were added. The mixing was continued for 2 minutes and then the material was discharged. The remaining steps were the same as in Example 1.
[0066] Comparative Example 3
[0067] The composition of the inner sheath material in this comparative example is the same as that in Example 1, except that hydrotalcite and zinc borate are added simultaneously.
[0068] The resin melting and main wetting of aluminum hydroxide and magnesium hydroxide were completed according to the method of Example 1. After the material temperature was reduced to 119°C, hydrotalcite and zinc borate were added at the same time, and the mixture was continued for 2.5 minutes. Then, silicone masterbatch, lubricant and color masterbatch were added, and the mixture was discharged after 2 minutes. The remaining steps were the same as in Example 1.
[0069] Comparative Example 4
[0070] The composition of the inner sheath material in this comparative example is the same as that in Example 1, except that zinc borate is added before hydrotalcite.
[0071] The main wettation of aluminum hydroxide and magnesium hydroxide was completed according to the method of Example 1. After the material temperature was reduced to 119°C, zinc borate was added and mixed for 2 minutes, followed by the addition of hydrotalcite and continued mixing for 2.5 minutes. Then, silicone masterbatch, lubricant and color masterbatch were added and mixed for 1.5 minutes before discharge. The remaining steps were the same as in Example 1.
[0072] Comparative Example 5
[0073] The composition of the inner sheath material and the other preparation conditions in this comparative example are the same as those in Example 1. The difference is that the mixing time of the hydrotalcite is shortened to 1.0 min, so that the V2 / V1 after hydrotalcite treatment is 0.795. Then, zinc borate, silicone masterbatch, lubricant and color masterbatch are added according to the method of Example 1, and the mixing and two-stage extrusion granulation are completed.
[0074] Comparative Example 6
[0075] The composition of the inner sheath material and the other preparation conditions in this comparative example are the same as those in Example 1. The difference is that the mixing time of the hydrotalcite is extended to 3.5 min, so that the V2 / V1 after hydrotalcite treatment is 0.519. Then zinc borate, silicone masterbatch, lubricant and color masterbatch are added and mixed for 1.5 min before being discharged. The total time from adding hydrotalcite to discharge is 5 min. Then, two-stage extrusion granulation is carried out according to the conditions of Example 1.
[0076] The irradiated cross-linked polyethylene insulation material used in all embodiments and comparative examples, based on a total resin matrix of 100 parts, includes 48 parts linear low-density polyethylene, 24 parts ethylene-vinyl acetate copolymer, 18 parts polyolefin elastomer, and 10 parts maleic anhydride grafted polyethylene, with the addition of 65 parts aluminum hydroxide, 25 parts magnesium hydroxide, 4 parts zinc borate, 2.5 parts silicone masterbatch, 1.8 parts trimethylolpropane trimethacrylate, 1.0 part composite antioxidant, 0.8 parts lubricant, and 1.0 part color masterbatch.
[0077] The maleic anhydride grafting rate of the maleic anhydride-grafted polyethylene used in the insulation material is 0.8%, the purity of trimethylolpropane trimethacrylate is ≥98%, and the other raw materials of the same name use the same specifications as mentioned above.
[0078] Before preparing the insulating material, aluminum hydroxide, magnesium hydroxide and zinc borate were dried at 95°C for 3 hours. Linear low-density polyethylene, ethylene-vinyl acetate copolymer, polyolefin elastomer and maleic anhydride grafted polyethylene were added to a high-speed mixer and mixed at 70°C for 5 minutes. Then, dried aluminum hydroxide, magnesium hydroxide and zinc borate were added, along with silicone masterbatch, composite antioxidant and lubricant, and the mixture was continued to be mixed for 8 minutes.
[0079] Reduce the mixing speed of the high-speed mixer, add trimethylolpropane trimethacrylate and color masterbatch, and continue mixing for 3 minutes to obtain the insulation premix.
[0080] The obtained insulating material premix is added to a mixer and mixed at 120°C until all resins are fully melted and the mixing torque tends to be stable. The mixture is then discharged and sent to a two-stage extrusion granulation equipment. The material temperature of the first-stage twin-screw extruder is controlled at 120-135°C, and the die temperature of the second-stage single-screw extruder is controlled at 125-135°C. After pelleting and cooling, the extrudate is dried at 70°C for 2 hours and then sealed for storage.
[0081] The low-smoke halogen-free outer sheath material used in all embodiments and comparative examples, based on a total resin matrix of 100 parts, includes 40 parts ethylene-vinyl acetate copolymer, 18 parts linear low-density polyethylene, 18 parts polyolefin elastomer, 12 parts metallocene polyethylene and 12 parts maleic anhydride grafted polyolefin, and adds 105 parts aluminum hydroxide, 40 parts magnesium hydroxide, 7 parts zinc borate, 4 parts hydrotalcite, 3 parts silicone masterbatch, 1.2 parts composite antioxidant, 1.5 parts lubricant and 1.5 parts black masterbatch. The same raw materials used are of the same specifications as the inner sheath material.
[0082] In preparing the outer sheath material, aluminum hydroxide, magnesium hydroxide, hydrotalcite, and zinc borate were dried at 100°C for 3 hours. Ethylene-vinyl acetate copolymer, linear low-density polyethylene, polyolefin elastomer, metallocene polyethylene, and maleic anhydride-grafted polyolefin were added to a high-speed mixer and mixed at 70°C for 5 minutes. Then, all aluminum hydroxide, magnesium hydroxide, hydrotalcite, and zinc borate were added, along with silicone masterbatch, composite antioxidant, lubricant, and black masterbatch. The mixture was then mixed for another 8 minutes to obtain the outer sheath material premix.
[0083] The premixed outer sheath material is added to a mixer and mixed at 125-135℃ until all resins are fully melted and the torque remains stable. The mixture is then discharged and fed into a two-stage extrusion granulation equipment. The material temperature of the first-stage twin-screw extruder is controlled at 120-140℃, and the die head temperature of the second-stage single-screw extruder is controlled at 125-140℃. The highest material temperature during the granulation process does not exceed 145℃. The resulting granules are cooled, dried, and then sealed for storage.
[0084] Aluminum hydroxide, magnesium hydroxide, hydrotalcite, and zinc borate in the outer sheath material are added in the same mixing stage, without controlling the degree of finite termination of hydrotalcite.
[0085] The inner sheath materials prepared in the above embodiments and comparative examples were dried at 70°C for 2 hours and used in conjunction with a common irradiated cross-linked polyethylene insulation material, CAT6 SFTP network unit and low smoke halogen-free outer sheath material to prepare power composite cables under the same manufacturing conditions.
[0086] Fifty annealed soft copper wires with a diameter of 0.25±0.003mm were stranded to the left with a pitch of 50mm. An insulation layer with a nominal thickness of 0.70mm was extruded over the resulting stranded copper conductor. The conductor was then subjected to electron beam irradiation treatment with an electron beam energy of 2.0MeV and an absorbed dose of 130kGy. The irradiated power conductor core was then relaxed at 60℃ for 6 hours and then left to stand at 25℃ for 18 hours.
[0087] Three power line cores were prepared using the above method, and CAT6SFTP network units of the same batch, structure and specifications were selected.
[0088] Three power conductor cores, one CAT6 SFTP network unit, and a low-smoke halogen-free flame-retardant polypropylene filler rope are twisted together. The tension of the power conductor cores is 16N, the tension of the CAT6 SFTP network unit is 11N, the tension of the filler rope is 7N, the cable pitch is 160mm, and the cable core gap filling rate is 95%.
[0089] Polyester film tape and low-smoke halogen-free glass fiber reinforced flame-retardant tape are wrapped around the outside of the composite cable core in sequence, and then tin-plated soft copper wire is used to braid the total shielding layer, with a braiding coverage rate of 82%.
[0090] The inner sheath materials prepared in each embodiment and comparative example were used to extrude a low-smoke halogen-free inner sheath with a nominal thickness of 1.15 mm outside the total shielding layer. After the inner sheath left the die head, it was first air-shaped and then cooled by two water tanks with water temperatures of 40°C and 25°C.
[0091] Two layers of galvanized steel strips, each 0.20 mm thick, are wrapped around the outer sheath of a low-smoke halogen-free inner sheath, and then a low-smoke halogen-free outer sheath with a nominal thickness of 1.8 mm is extruded to obtain the power composite cable corresponding to each embodiment and comparative example.
[0092] The inner sheath materials and corresponding power composite cables prepared in each embodiment and comparative example are tested, and the test results are compared and analyzed.
[0093] Experimental Example 1
[0094] To compare the torque changes during the mixing process and the changes in the acid value of the extractable polymer phase before and after the addition of hydrotalcite in each embodiment and comparative example, the bulk wetting state of aluminum hydroxide and magnesium hydroxide and the degree of limited termination of hydrotalcite were characterized.
[0095] Three batches of sheathing material were prepared independently within each group, using the same internal mixer with an effective volume of 5L, a filling factor of 0.70±0.02, and a rotor speed of 50r / min. Before the test, the mixing chamber was preheated to 115℃ and run unloaded for 10min. After the temperature and torque readings stabilized, feeding began. The torque data was collected once per second. The feeding amount was determined according to the same filling factor for each group. The feeding mass, initial equipment temperature, and rotor speed of the three batches of samples in the same group were kept consistent. The samples prepared in this experimental example were only used for process sampling and condition monitoring.
[0096] For Examples 1-5 and Comparative Examples 3-6, each resin and composite antioxidant were mixed until fully melted, and then aluminum hydroxide and magnesium hydroxide were added. Torque data were continuously collected from the time aluminum hydroxide and magnesium hydroxide were added until the next stage of feeding was completed.
[0097] Torque data for Comparative Example 1 were collected starting after aluminum hydroxide, magnesium hydroxide, hydrotalcite, zinc borate, and other additives were added, and continued until the end of the co-mixing stage. Torque data for Comparative Example 2 were collected starting after aluminum hydroxide, magnesium hydroxide, and hydrotalcite were added, and continued until before the addition of zinc borate and other additives. The torque data for Comparative Example 1 and Comparative Example 2 were used only to compare changes in the corresponding mixing stages and were not used as the basis for determining the main wetting endpoint.
[0098] For groups with an independent wetting stage, the highest torque that occurs after the addition of aluminum hydroxide and magnesium hydroxide is denoted as the peak torque M. p Within the range that meets the stability requirement for 60-90 seconds, the average torque over the 60 seconds preceding the end of this phase is taken as the stable torque M. s Peak torque M p With stable torque M s The difference accounts for the peak torque M p The percentage is taken as the torque reduction rate.
[0099] Calculate the sampled torque and the stable torque M for each of the above 60 consecutive seconds. s The deviation between them is expressed as the absolute value of the deviation as a percentage of the stable torque M. s The percentages are expressed as a percentage, and the maximum value is taken as the torque fluctuation rate; the peak torque, stable torque, torque decrease rate and torque fluctuation rate of the corresponding mixing stages are calculated using the same method for Comparative Example 1 and Comparative Example 2.
[0100] For Examples 1-5, Comparative Examples 5 and 6, approximately 30g of samples were taken after aluminum hydroxide and magnesium hydroxide were fully wetted and before the addition of hydrotalcite. Approximately 30g of samples were taken again after the hydrotalcite was mixed according to the specified conditions for each group.
[0101] For Comparative Example 3, approximately 30g of sample was taken after aluminum hydroxide and magnesium hydroxide had finished wetting the main body and before hydrotalcite and zinc borate were added simultaneously. Approximately 30g of sample was taken again after hydrotalcite and zinc borate were mixed together. For Comparative Example 4, approximately 30g of sample was taken after zinc borate was mixed and before hydrotalcite was added. Approximately 30g of sample was taken again after hydrotalcite was mixed.
[0102] Comparative Examples 1 and 2 did not form independent stages before and after the addition of hydrotalcite, so V1, V2, and V2 / V1 were not measured. The acid value change of Comparative Example 3 was affected by the combined addition of hydrotalcite and zinc borate. The sample of Comparative Example 4 had been mixed with zinc borate before the addition of hydrotalcite. Therefore, the V2 / V1 obtained in the two groups can only be used as the apparent acid value ratio under the corresponding feeding sequence.
[0103] Each sample was immediately pressed into a thin sheet with a thickness of no more than 2 mm after being taken out, and placed between two cooling metal plates to cool the sample to below 40°C within 2 minutes. The sample was then sealed and stored, and the acid value was determined within 24 hours.
[0104] Weigh 5.00g of test samples before and after the addition of hydrotalcite, cut them to a particle size of no more than 2mm, add 150mL of xylene, heat to reflux and maintain for 60min, filter while hot using a glass fiber filter membrane after reflux, wash the filter residue twice with 20mL of hot xylene, and combine the filtrate and washing liquid.
[0105] The obtained liquid was subjected to reduced pressure to remove the solvent at a temperature not exceeding 80°C. After each reduction drying, the liquid was cooled to room temperature and weighed until the mass difference between two consecutive weighings was no greater than 2 mg. The extractable polymer phase was then obtained and its mass m was recorded.
[0106] The obtained extractable polymer phase was completely dissolved in a mixed solvent of xylene and isopropanol with a volume ratio of 2:1. Potentiometric titration was performed using a 0.05 mol / L potassium hydroxide ethanol standard solution, with the equivalence point of the potentiometric titration curve as the titration endpoint. A blank test was also performed using the same volume of the mixed solvent.
[0107] The potassium hydroxide ethanol standard solution was calibrated with potassium hydrogen phthalate on the day of use. Each sample was measured twice in parallel. The relative deviation between the two measurements was no more than 3%, and the average value was taken as the result of the batch of samples.
[0108] The acid value of the extractable polymer phase is calculated according to the following formula:
[0109]
[0110] In the formula, V is the acid value of the extractable polymer phase, in mgKOH / g; c is the actual concentration of the potassium hydroxide ethanol standard solution, in mol / L; v is the volume of standard solution consumed by the sample, in mL; v0 is the volume of standard solution consumed by the blank test, in mL; and m is the mass of the extractable polymer phase, in g.
[0111] The extractable polymer phase acid value of the sample before the addition of hydrotalcite was recorded as V1. The extractable polymer phase acid value of the sample after the hydrotalcite was mixed according to the specified conditions of each group was recorded as V2. V2 / V1 was calculated for each batch of samples. The results of each group were expressed as the average and standard deviation of the three batches of samples. The results are shown in Table 1.
[0112] Table 1. Results of determination of bulk wetting and finite termination state of sheath material in each group.
[0113]
[0114] As shown in Table 1, after adding aluminum hydroxide and magnesium hydroxide, the mixing torque of Examples 1-5 decreased from the peak value and gradually stabilized. The acid values of the extractable polymer phases before the addition of hydrotalcite were similar in each group, indicating that the main wetting stage had a consistent basis for comparison.
[0115] In Examples 2 and 3, only the mixing time of the hydrotalcite was changed, and V2 / V1 decreased as the mixing time was extended, indicating that the mixing time of the hydrotalcite affects the degree of finite termination. In Examples 4 and 5, after changing the amount of hydrotalcite, V2 / V1 also changed, but the magnitude of the change was not consistent with the change in the amount of hydrotalcite, indicating that the degree of finite termination is not determined solely by the amount of hydrotalcite.
[0116] Comparative Examples 1 and 2 did not separate the main wetting of aluminum hydroxide and magnesium hydroxide from the treatment of hydrotalcite, and the torque fluctuations in the corresponding mixing stages were higher than those in the embodiments, and no independent main wetting stage was formed as in the embodiments. Although the main wetting conditions remained unchanged in Comparative Examples 5 and 6, V2 / V1 were higher and lower respectively due to the different mixing times of hydrotalcite, indicating that both too short and too long mixing times would change the degree of finite termination.
[0117] Comparative Example 3 added hydrotalcite and zinc borate simultaneously, while Comparative Example 4 added zinc borate first and then hydrotalcite. The V2 / V1 ratios obtained in both groups were affected by the order of feeding and could not reflect the finite termination degree of hydrotalcite alone. The results in Table 1 show that the wettability of the main body, V2 / V1, and the order of adding inorganic components all affect the state of the inner sheath material during the mixing process.
[0118] Experiment Example 2
[0119] To compare the differences in mechanical properties, thermal aging properties, flame retardant and smoke-suppressing properties, and high-temperature pressure performance of the inner sheath materials prepared in each embodiment and comparative example, the following tests were conducted.
[0120] The sheathing material in each group was taken from three independently prepared batches of granules. After drying the granules at 70℃ for 2 hours, they were pressed into sheets using a flat vulcanizing machine at a pressing temperature of 165℃. The sheets were first preheated for 5 minutes without pressure, then held at 10MPa for 5 minutes, and then cooled to below 40℃ while maintaining the pressure. Test pieces with thicknesses of 2.0±0.1mm, 3.0±0.1mm, and 6.0±0.2mm were obtained. All test pieces were placed in an environment of 23±2℃ and 50±5% relative humidity for 24 hours before testing.
[0121] Tensile specimens were cut from a piece with a thickness of 2.0±0.1 mm and a gauge length of 25 mm. The tensile speed was 250 mm / min. Five specimens were tested in each batch, and the tensile strength and elongation at break were recorded.
[0122] Shore hardness was measured using a specimen with a thickness of 2.0 ± 0.1 mm. During the test, the specimens were stacked until the total thickness was not less than 6 mm. The indenter was in contact with the specimen for 15 seconds before the reading was taken. Five mutually spaced positions were selected from each batch of specimens for measurement and the average value was taken.
[0123] The thermal aging test uses the same specimens as the tensile test. The specimens are placed in a hot air aging chamber at 100±2℃ for 168h, and then placed at 23±2℃ for 16h. The tensile strength is then measured under the same conditions. The ratio of the tensile strength after aging to the tensile strength before aging is taken as the tensile strength retention rate.
[0124] Oxygen index samples were cut from a specimen with a thickness of 3.0±0.1mm, and the sample size was 100mm×6.5mm×3.0mm. Five samples were tested in each batch and the average value was taken.
[0125] The smoke density sample was cut from a specimen with a thickness of 3.0 ± 0.1 mm, and the sample size was 75 mm × 75 mm × 3.0 mm. The external heating radiation intensity during the test was 25 kW / m². 2 The maximum specific optical density was recorded within 20 minutes by igniting a flame.
[0126] The high-temperature compressive stress relaxation specimen was cut from a specimen with a thickness of 6.0±0.2mm. The specimen size was 20mm×20mm×6mm. The initial thickness of the specimen was measured and recorded as h0. The specimen was then placed in a material testing machine with a constant temperature chamber and preheated at 70±1℃ for 30min. It was then compressed to 80% of the initial thickness at a speed of 1mm / min.
[0127] After reaching the specified compression amount, hold for 30 seconds and record the compressive stress at this time as the initial compressive stress σ0. Continue to hold for 4 hours after reaching the specified compression amount and record the compressive stress at 4 hours as σ4. The ratio of σ4 to σ0 is expressed as a percentage and is used as the compressive stress retention rate.
[0128] Immediately after the compression test, the load was removed, and the specimen was placed at 23±2℃ for 24 hours. The recovered thickness was measured and recorded as h. 24 h 24 The percentage of the difference between h0 and 0.8h0 is taken as the thickness recovery rate. Five compression samples are tested for each batch of inner sheath material and the average value is taken.
[0129] The test results were first taken as the average value of parallel samples in the same batch, and then expressed as the average value and standard deviation of the three batches of samples. The test results of mechanical properties, thermal aging properties and flame retardant and smoke suppression properties are shown in Table 2, and the test results of high temperature compressive stress relaxation and thickness recovery properties are shown in Table 3.
[0130] Table 2 Mechanical, thermal aging, and flame retardant and smoke-suppressing properties of sheath materials in each group
[0131]
[0132] Table 3. High-temperature compressive stress relaxation and thickness recovery properties of sheath materials in each group
[0133]
[0134] To compare the effects of hydrotalcite mixing time on finite termination and high-temperature compressive properties, Examples 1-3 and Comparative Examples 5-6, with identical composition and other preparation conditions but different hydrotalcite mixing times, were selected. The relationships between hydrotalcite mixing time and V2 / V1, compressive stress retention rate, and thickness recovery rate were plotted. Figure 1 .
[0135] As shown in Table 2, the tensile strength, elongation at break, Shore hardness, and tensile strength retention rate after heat aging of the embodiments are similar, and the oxygen index and maximum specific optical density do not fluctuate significantly. The limited termination treatment does not weaken the mechanical properties, heat aging resistance, and flame retardant and smoke-suppressing properties of the inner sheath material.
[0136] From Table 3 and Figure 1 It can be seen that, under the same composition of the inner sheath material and other preparation conditions, as the mixing time of hydrotalcite increased from 1.0 min to 3.2 min, the V2 / V1 ratio and compressive stress retention rate gradually decreased, while the thickness recovery rate increased from 92.1% to 95.4%. When the mixing time of hydrotalcite was extended to 3.5 min, the V2 / V1 ratio and compressive stress retention rate continued to decrease, but the thickness recovery rate dropped to 84.8%. This indicates that when the finite termination degree is insufficient, the stress release of the inner sheath material during high-temperature compression is not sufficient, and when it is too high, it weakens the dimensional recovery ability after unloading.
[0137] Comparative Example 1 used co-mixing, Comparative Example 3 added hydrotalcite and zinc borate simultaneously, and Comparative Example 4 added zinc borate first and then hydrotalcite. The compressive stress retention rates of Comparative Example 1 were higher than those of the embodiments. The apparent V2 / V1 of Comparative Example 3 was similar to that of some embodiments, but the same compressive stress relaxation performance was not obtained, indicating that V2 / V1 needs to be evaluated in conjunction with the order of addition of inorganic components.
[0138] Comparative Example 2 added hydrotalcite before the main body was wetted. Its tensile, thermal aging and smoke suppression properties were all lower than those of the Example. Comparative Example 5 had insufficient finite termination and the compressive stress retention rate was still at a high level. Although the compressive stress retention rate of Comparative Example 6 was lower than that of the Examples, its tensile strength, tensile strength retention rate after thermal aging, oxygen index and thickness recovery rate all decreased, and the maximum specific optical density increased. The inner sheath material needs to maintain basic properties, compressive stress relaxation ability and dimensional recovery ability after unloading at the same time.
[0139] Experimental Example 3
[0140] To compare the network transmission performance of the power composite cables in each embodiment and comparative example before and after current-carrying thermal cycling, three 30m long samples were cut from each group of power composite cables. The samples were placed in an environment of 23±2℃ and 50±5% relative humidity for 24 hours before initial testing.
[0141] Each sample was coiled on a non-metallic winding spool with a diameter of 1.0m. The spacing between adjacent coils was not less than 30mm. The coiling position remained unchanged during the test. Shielded Category 6 connection modules of the same batch were installed at both ends of the CAT6 SFTP network unit. The connection modules and 1m long cables at both ends were placed outside the environmental test chamber. After the connection was completed, they were not disassembled or re-terminated.
[0142] The transmission performance of the CAT6 SFTP network unit was determined using a calibrated network cable analyzer at a frequency of 1-250MHz. Tests were performed from both ends of the sample, and the measured parameters included characteristic impedance, insertion loss, return loss, near-end crosstalk, and equal-level far-end crosstalk.
[0143] In the test results of the four pairs of wires, the maximum absolute difference between the characteristic impedance and 100Ω in the test frequency band is taken as the maximum impedance deviation, and the minimum difference between the measured return loss and the corresponding frequency limit is taken as the minimum return loss margin. The near-end crosstalk margin and the equal-level far-end crosstalk margin are determined in the same way. The insertion loss of 250MHz is taken as the maximum value among the four pairs of wires.
[0144] After the initial test was completed, each sample was placed in an environmental test chamber at a temperature of 25±2℃, and the three power conductors were connected in series to a low-voltage AC high-current power supply. The current was adjusted to raise the temperature of the power conductors.
[0145] The average conductor temperature of the electric field conductor core was determined using the conductor resistance method. After the sample was placed in an environment of 20±1℃ and the temperature stabilized, the resistance of the three conductors connected in series was measured and recorded as R. 20 During the current-carrying heating process, the power supply is briefly disconnected, and the conductor resistance at the corresponding moment is measured and recorded as R. t The conductor temperature is calculated according to the following formula:
[0146]
[0147] In the formula, T is the conductor temperature, in °C; R 20 R is the resistance of three conductors connected in series at 20℃, expressed in Ω. t The resistance of the three conductors connected in series at the time of measurement is given in Ω; 0.00393 is the temperature coefficient of resistance of the copper conductor at 20℃.
[0148] Each current-carrying thermal cycle includes four stages: heating, holding, cooling, and stabilization. The current is adjusted to raise the temperature of the power conductor from 25°C to 70±2°C within 45-60 minutes, and then maintain it at 70±2°C for 120 minutes. After that, the power is disconnected, and the sample is cooled to 25±2°C within 90 minutes. After being left to stand for another 30 minutes, the next cycle begins. Each group of samples undergoes 100 current-carrying thermal cycles.
[0149] After completing 100 current-carrying thermal cycles, each sample was placed in an environment of 23±2℃ for 12 hours. Then, the transmission performance of the CAT6 SFTP network unit was determined according to the initial test method. During the test, the power line core was kept de-energized, and the coiling position and connection status of the sample remained unchanged.
[0150] The insertion loss increment was obtained by subtracting the initial insertion loss from the 250MHz insertion loss after 100 current-carrying thermal cycles. The test results for each group are expressed as the average value ± standard deviation of 3 independent samples. The test results before thermal cycling are shown in Table 4, and the test results after 100 current-carrying thermal cycles are shown in Table 5.
[0151] Three additional CAT6 SFTP network units, each 30m in length and made from the same batch of materials, and not combined with the power line core, were taken as blank samples. They were coiled and terminated in the same way as the power composite cable samples. The blank samples were placed in an independent environmental test chamber and subjected to 100 temperature cycles according to the time program of raising the temperature from 25±2℃ to 70±2℃, holding for 120 minutes, lowering the temperature to 25±2℃ and stabilizing for 30 minutes. The transmission performance before and after the cycle was determined according to the aforementioned method.
[0152] Table 4. Network transmission performance of each group of power composite cables before thermal cycling.
[0153]
[0154] Table 5. Network transmission performance of each group of power composite cables after 100 current-carrying thermal cycles.
[0155]
[0156] To compare the changes in the cross-sectional shape of the CAT6 SFTP network unit before and after current-carrying thermal cycling, after 100 current-carrying thermal cycles, five 10mm long samples were cut from the middle of each power composite cable. The maximum and minimum outer diameters of the network unit sheath on the cross-section of each sample were measured using an image measuring instrument. The percentage of the difference between the maximum and minimum outer diameters to the maximum outer diameter was taken as the cross-sectional ellipticity. In addition, five samples were cut from three power composite cables prepared in the same batch in each group that had not undergone current-carrying thermal cycling, and the initial cross-sectional ellipticity was measured. The average value of the five cross-sections was taken as the measurement result for each cable. The results of each group were expressed as the average value and standard deviation of the measurement results of three independent cables. The measurement results before and after thermal cycling and the increase in ellipticity are shown in Table 6.
[0157] Table 6 Ellipticity of Network Unit Cross-sections Before and After Thermal Cycling of Each Group of Power Composite Cables
[0158]
[0159] As shown in Table 4, the maximum impedance deviation, return loss margin, crosstalk margin, and insertion loss of each group of power composite cables are similar before the current-carrying thermal cycling, which provides a basis for comparing the changes in transmission performance after thermal cycling.
[0160] As shown in Tables 5 and 6, after 100 current-carrying thermal cycles, the changes in impedance, return loss, crosstalk, and insertion loss in the embodiments are all smaller than those in the comparative examples, and the increase in the ellipticity of the network cell cross section does not exceed 1.2%. This indicates that the inner sheath used in each embodiment can reduce the impact of repeated temperature rises and falls on the cross-sectional shape and transmission performance of the network cell.
[0161] After changing the mixing time of hydrotalcite in Examples 2 and 3, the compressive stress retention rate and the transmission parameters after thermal cycling changed accordingly. However, Example 3, which had a lower compressive stress retention rate, did not outperform Example 1 in all transmission indicators. Examples 4 and 5 also showed different transmission performance changes after changing the amount of hydrotalcite, indicating that the thermal cycling adaptability of the inner sheath cannot be judged solely based on the amount of hydrotalcite or the compressive stress retention rate.
[0162] The changes in transmission parameters and the increase in cross-sectional ellipticity after thermal cycling in Comparative Examples 1-4 were greater than those in the embodiments, indicating that the inner sheath's ability to maintain the cross-sectional shape of the network unit decreased after the sequence of body wetting, hydrotalcite finite termination, and zinc borate addition was changed.
[0163] Comparative Example 5 had a shorter hydrotalcite mixing time, and the changes in transmission parameters after thermal cycling were still higher than those in the other examples. Although Comparative Example 6 had a lower compressive stress retention rate, its thickness recovery rate was low, and the changes in the ellipticity of the network unit cross section and transmission parameters were large. This indicates that insufficient or excessive hydrotalcite treatment is not conducive to the dimensional stability of the inner sheath during repeated heating and cooling processes.
[0164] After being cycled at the same temperature, the blank network units showed little change in various transmission parameters, indicating that the differences in transmission performance between the groups of power composite cables did not mainly come from the temperature aging of the network units themselves, but were related to the changes in the internal constraint state of the composite cables.
[0165] Based on the comprehensive experimental results, adding hydrotalcite after aluminum hydroxide and magnesium hydroxide have completed the main wetting process, followed by the addition of zinc borate and other additives, can reduce the impact of current-carrying thermal cycling on the cross-sectional shape and transmission performance of CAT6 SFTP network units while maintaining the mechanical, heat-resistant aging, and flame-retardant smoke-suppressing properties of the inner sheath material.
[0166] The technical scope of this invention is not limited to the content described above. Those skilled in the art can make various modifications and variations to the above embodiments without departing from the technical concept of this invention, and all such modifications and variations should fall within the protection scope of this invention.
Claims
1. A method for preparing a cross-linked polyethylene insulated low-smoke halogen-free power composite cable, characterized in that, Includes the following steps: S1: Add ethylene-vinyl acetate copolymer, linear low-density polyethylene, polyolefin elastomer, metallocene polyethylene and maleic anhydride grafted polyolefin into a mixer and mix at 110-120℃ until all resins are fully melted to obtain molten material. S2: Add all aluminum hydroxide and magnesium hydroxide to the molten material, raise the material temperature to 125-135℃, and continue to knead for 4-8 minutes to obtain the main wetted material; S3: Reduce the temperature of the main wetting material to 115-123℃, add hydrotalcite and continue mixing. Record the extractable polymer phase acid value of the main wetting material before adding hydrotalcite as V1, and record the extractable polymer phase acid value of the material after mixing with hydrotalcite as V2. V2 / V1 is 0.55-0.
75. S4: After mixing, zinc borate is added to the material, and after mixing, the material is discharged. The resulting mixture is then extruded and granulated to obtain low-smoke halogen-free inner sheath material. S5: A composite cable core is formed by stranding together a power conductor core with an irradiated cross-linked polyethylene insulation layer, a CAT6 SFTP network unit, and a low-smoke halogen-free flame-retardant filler material. A first wrapping layer, a second wrapping layer, and a total shielding layer are formed sequentially outside the composite cable core. The low-smoke halogen-free inner sheath material is extruded outside the total shielding layer to form a low-smoke halogen-free inner sheath. Then, a steel tape armor layer and a low-smoke halogen-free outer sheath are formed sequentially to obtain a power composite cable.
2. The method for preparing cross-linked polyethylene insulated low-smoke halogen-free power composite cable according to claim 1, characterized in that: In S2, after aluminum hydroxide and magnesium hydroxide are added, the mixing torque first rises to the peak value, and then gradually decreases during the mixing process. When the torque decreases by 12-22% relative to the peak value, and the torque fluctuation within the following 60-90 seconds does not exceed ±3% of the stable torque value, the main body wetting is ended.
3. The method for preparing cross-linked polyethylene insulated low-smoke halogen-free power composite cable according to claim 1, characterized in that: In S3, after adding hydrotalcite, continue mixing for 1.5-3.5 minutes to perform a limited termination treatment on the main wetted material.
4. The method for preparing cross-linked polyethylene insulated low-smoke halogen-free power composite cable according to claim 3, characterized in that: After the limited termination treatment, maintain the material temperature at 112-122℃, add zinc borate, silicone masterbatch, lubricant and color masterbatch, and continue mixing for 1.5-3 minutes before discharging.
5. The method for preparing cross-linked polyethylene insulated low-smoke halogen-free power composite cable according to claim 1 or 3, characterized in that: The total time from adding the hydrotalcite to the internal mixer to the discharge of the material shall not exceed 5 minutes.
6. The method for preparing cross-linked polyethylene insulated low-smoke halogen-free power composite cable according to claim 1, characterized in that: Before preparing the low-smoke halogen-free inner sheath material, aluminum hydroxide, magnesium hydroxide, hydrotalcite and zinc borate are dried at 95-105℃ for 2-4 hours.
7. The method for preparing cross-linked polyethylene insulated low-smoke halogen-free power composite cable according to claim 6, characterized in that: The free water content of the aluminum hydroxide and magnesium hydroxide is not higher than 0.2%, and the free water content of the hydrotalcite and zinc borate is not higher than 0.5%.
8. A cross-linked polyethylene insulated low-smoke halogen-free power composite cable prepared by the method according to any one of claims 1-7, characterized in that, It includes a composite cable core and a first wrapping layer, a second wrapping layer, a total shielding layer, a low-smoke halogen-free inner sheath, a steel tape armor layer, and a low-smoke halogen-free outer sheath that are sequentially wrapped around the composite cable core. The material of the low-smoke halogen-free inner sheath, based on a total resin matrix of 100 parts, includes 40-48 parts of ethylene-vinyl acetate copolymer, 16-24 parts of linear low-density polyethylene, 18-26 parts of polyolefin elastomer, 5-10 parts of metallocene polyethylene and 8-12 parts of maleic anhydride-grafted polyolefin, 90-105 parts of aluminum hydroxide, 28-40 parts of magnesium hydroxide, 3-5 parts of hydrotalcite and 4-7 parts of zinc borate.
9. The cross-linked polyethylene insulated low-smoke halogen-free power composite cable according to claim 8, characterized in that: The composite cable core is formed by stranding together a power wire core with an irradiated cross-linked polyethylene insulation layer, a CAT6 SFTP network unit, and a low-smoke halogen-free flame-retardant filler material.
10. The cross-linked polyethylene insulated low-smoke halogen-free power composite cable according to claim 8, characterized in that: Based on a total resin matrix of 100 parts, the material of the low-smoke halogen-free inner sheath also includes 2-4 parts of silicone masterbatch, 0.8-1.5 parts of composite antioxidant, 1.0-2.0 parts of lubricant and 1.0-2.0 parts of color masterbatch.
Citation Information
Patent Citations
Network electricity composite cable
CN114093555A
Irradiation crosslinking high-electrical-property low-temperature-resistant low-smoke halogen-free insulating material as well as preparation method and application thereof
CN116102815A
B1-grade cable material as well as preparation method and application thereof
CN119684704A
